Challenges and Opportunities for Regional Policy in Mexico - Suarez Paniagua, Susana (Advances in Social Sciences Research Journal, 2017)
In Mexico, the regions have long been experiencing great economic and social disparities in terms of per capita income, family income, schooling, housing, social services, infrastructure, transportation; institutional development, social participation, among other items. Disparities that constitute the challenges facing the Government of Mexico to promote and achieve greater economic and social development of the country with greater balance. Challenges that force the State to rethink the country’s course of development and with it a new conception and instrumental design of a regional policy that promotes essential processes of economic and social competitiveness of its different regions and the country. The purpose of this paper is to analyze the regional policy of the Mexican government in recent years and to compare it with the regional policies of the European Union to examine the mechanisms that can trigger regional development processes that can be considered in the indispensable construction of a new design and implementation of regional policy.